The Impact of Administrative Capacity on Disaster Management in Nigeria: A Study of the National Emergency Management Agency in Niger Delta Region - Omoyemi, Haruna A. Joy; Onofere Princewill Okereka (Master Program of Sociology, Universitas Malikussaleh, 2025)
Disaster management effectiveness is crucial in mitigating the adverse effects of natural and human-induced disasters, particularly in disaster-prone regions like the Niger Delta, Nigeria. This study examined the impact of administrative capacity on disaster management, focusing on the National Emergency Management Agency (NEMA) in selected states within the Niger Delta region. Specifically, the study investigated the influence of resource availability, personnel capacity, and coordination mechanisms on disaster response and management effectiveness. A cross-sectional research design was adopted, and data was collected via a survey of four hundred (400) respondents. Out of the 400-questionnaire administered, only 338 were retrieved and analyzed. The study was anchored on structural-functionalism theory as its theoretical framework. The theory explains how public trust and compliance with disaster management depends on shared values and effective governance. If NEMA is transparent, accountable, and effective, citizens are more likely to cooperate during evacuations, relief distribution, and disaster preparedness initiatives. Data collected were analyzed using percentages, frequency, Pearson’s coefficient of correlation, and multiple regression analysis with the aid of the Statistical Package for Social Science (SPSS) version 23. The results of the study showed that availability of resources, capacity of personnel and coordination mechanisms positively and significantly affect disaster management effectiveness by NEMA in selected states within the Niger Delta region. The study concluded that enhancing administrative capacity through increased resource allocation, personnel development, and improved coordination mechanisms is essential for strengthening disaster management in Niger Delta region in particular, and Nigeria in general. The findings provide valuable insights for policymakers, emergency response agencies, and stakeholders in developing strategic frameworks to improve disaster preparedness, response, and recovery efforts. The study recommended among others that the government should prioritize funding and resource allocation for disaster management, ensuring that NEMA has access to sufficient financial, logistical, and technological resources to improve resilience, emergency preparedness, response, and recovery efforts in the Niger Delta against disasters.